Resources: Gender - International Food Policy Research Institute (International Food Policy Research Institute, 2019)
IFPRI’s mission is to provide research-based policy solutions to sustainably reduce poverty and end hunger and malnutrition. Recent open-access publications and websites address the role of gender, equity, and women’s empowerment in shaping and improving food security and nutrition outcomes in developing countries. For links to these and other resources: www.ifpri.org/topic/gender